Challenges and Considerations in Performing Laparoscopic Cholecystectomy in a Patient with Total Situs Inversus a Case Report - Flores Gonzalez, C J; Gonzàlez Martinez, A U; Durango Hernandez, D J; Lopez Bernal, C A; Mendoza Rodriguez, R; Hernandez Molina, M P; Montes Salas, J M H (British Journal of Healthcare and Medical Research, 2025)
Laparoscopic cholecystectomy plays a central role in the treatment of patients with gallstones and is the gold standard for the management. Total situs inversus (TSI) is a rare congenital anomaly in which there is a transposition of the thoracic and abdominal organs, resulting in a mirror-image left-right configuration of the normal anatomical placement of organs. TSI affects less than 0.01% of the population. We present a case of a 68-year-old male with cholelithiasis and TSI, managed with laparoscopic cholecystectomy using the American mirror technique for cholecystectomy in such patients, reporting favorable outcomes for the patient. In conclusion, bibliographic reports and our personal experience in this case emphasize that the unique anatomical disposition in TSI requires modifications to the surgical technique, necessitating a well-trained surgeon with a deep understanding of biliary anatomy and its variations.